Application of the Project Based Learning Model Assisted by Animation Media For Increase Liveliness Learning , Class V Social Sciences Lesson Content at SDN Bungingkela - Zeprianna; Sunarto Amus; Suyuti (Kirana Publisher (KNPub), 2024)
Education does not lah obtained with short , however it takes a long process . Education can become reject measuring progress something nation . Formulation problems with the Project Based Learning learning model , the use of animation media , the influence of the Project Based Learning model assisted by animation media For increase liveliness Study students on load social studies lesson for class V SDN Bungingkela . Research purposes application of the Project Based Learning learning model assisted by animation media For increase liveliness Study load social studies lesson for class V SDN Bungingkela . method study qualitative is method research based on philosophy​ postpositivism , used For examine the conditions natural object , ( as his opponent is experiment ) where researcher is a key instrument , technique data collection is carried out in a way triangulation ( combination ) , data analysis inductive / qualitative , and results study qualitative more emphasize meaning rather than generalizations . Research result develop potency student need done with apply a learning model innovative and constructive in the future will can increase ability student in understand subject matter.